PENGARUH PEMBERIAN MADU PADA LUKA DIABETES MELITUS UNTUK MEMPERCEPAT PROSES PENYEMBUHAN - Alfi Syahar Yakub; Heriansyah Heriansyah; Harliani Harliani; Muhammad Ikbal Arif (Jurusan Keperawatan Poltekkes Kemenkes Makassar, 2023)
Introduction : Diabetes is in the form of an increase in blood sugar levels or what is commonly called hyperglycemia beyond normal limits. This condition is a decrease in insulin secretion due to pancreatic dysfunction, decreased insulin sensitivity, or both (Ningsih Darwis & Graharti, 2019). According to the International Diabetes Federation (IDF), 425 million diabetics worldwide are aged 20-79 years. According to the World Health Organization (WHO), Indonesia is the 6th country in the world with the highest number of diabetics of more than 10 million people in Indonesia suffering from diabetes. Current treatment methods are very diverse, one of which is that honey can slow down the growth of bacteria so that there is an acceleration of wound healing. Objective : to find out the effect of honey removal on burns to speed up the healing process . Method : data collection and collection methods carried out through literature studies by searching the results of scientific publications with a time span of 2016- 2022 through the use of the Google Scholar Database, Garuda Portal and Pubmed. Results and Analysis : obtained 10 journals that discuss honey in diabetic wounds to speed up the healing process. Diabetic wounds show differences before and after honey feeding characterized by wounds becoming closed and the smell decreases. Discussion and Conclusion : Giving honey to diabetic wounds has an effect on accelerating the wound healing process. Honey also has a low pH can prevent the growth of germs. The high sugar content in honey can make the wound condition moist and will make the wound heal quickly